Q: How do you Factor 6x2 -13x 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x2 + 13x + 2 = (6x + 1)(x + 2).

It cannot be factored because the discriminant of b2-4ac is less than zero.

6 x 2 - 13 x + 5 = (3 x - 5) (2 x - 1) It is 11th grade algebra, and I'm in fourth, but I did get a little help from my big sis!!!

6xx - 13x + 6 = 0 6x2 - 13x + 6 = 0 (3x-2)(2x-3)=0 3x-2=0 or 2x-3=0 3x=2 or 2x=3 x=2/3 or x=3/2 x=0.667 or x=1.5

(x - 6)(x - 7)

Related questions

6x2+13x-5 = (2x+5)(3x-1) when factored

(3x + 7)(2x - 9)

6x2 - 13x - 63 = (2x - 9)(3x + 7). 6x2 - 13x - 63 since (6)(-63) = -(2*3*9*7) = (-27)(14),then -27 + 14 = -13, I write: = (6x - 27)(6x + 14)/3*2 = (2x - 9)(3x + 7)

6x2 - 13x - 63 = 6x2 + 14x - 27x - 63 = 2x(3x + 7) - 9(3x + 7) = (3x + 7)(2x - 9)

6x2 + 13x + 2 = (6x + 1)(x + 2).

It cannot be factored because the discriminant of b2-4ac is less than zero.

(2x - 9)(3x + 7)

6x2+13x-5 = 0 (2x+5)(3x-1) = 0 x = -5/2 or x = 1/3

6x2-18x+12 = (6x-6)(x-2)

6 x 2 - 13 x + 5 = (3 x - 5) (2 x - 1) It is 11th grade algebra, and I'm in fourth, but I did get a little help from my big sis!!!

6xx - 13x + 6 = 0 6x2 - 13x + 6 = 0 (3x-2)(2x-3)=0 3x-2=0 or 2x-3=0 3x=2 or 2x=3 x=2/3 or x=3/2 x=0.667 or x=1.5

(3x + 2)(2x - 3)